The impact of the COVID 19 pandemic on the occurrence of anxiety and depression in nursing students - Dujlović Gordana; Mikić Milena; Aranđelović Branimirka; Gajić Marijana; Tomić Sanja; Tomić Slobodan; Peričević-Medić Sonja (Association of Nurses Technicians and Midwives, 2023)
Introduction: The COVID-19 pandemic has increased the symptoms of significant psychological burdens for the entire population. However, little is known about the psychological effect of COVID-19 on healthcare students. Objective: The research aimed to determine whether and to what degree healthcare students exhibit signs and symptoms of anxiety and depression during the second year of the pandemic. Material and methods: The study was conducted as an online cross-sectional study, by surveying 133 healthcare students of the Faculty of Medicine. The questionnaire for the assessment of anxiety (General Anxiety Disorder - GAD-7) and the questionnaire for the assessment of depression (Patient Health Questionnaire - PHQ-9) were used as research instruments. Descriptive and inferential statistical methods were used for statistical data processing, and statistical significance was determined at the p≤ 0.05 level. Results: The highest percentage of students showed minimal symptoms of depression (40.6%), i.e. symptoms of minimal anxiety (45.1%), while the total average score of the GAD-7 questionnaire was 6.35±5.27(SD), and the average value of the total PHQ-9 score was 7.42±5.59(SD). Conclusion: The COVID-19 pandemic had an impact on healthcare students, who during the second year of the pandemic showed mild depression and mild anxiety.